Transcriptome profile of cup-shaped galls in Litsea acuminata leaves - Shih, Tin-Han (PLoS One, 2018)
BACKGROUND: Insect galls are atypical plant tissues induced by the invasion of insects. Compared to the host leaf, gall tissues lose photosynthetic ability, but have higher soluble sugar content. Although the physiological and biochemical regulation of gall tissues have been demonstrated, the mechanism of genetic regulation has only been analyzed in few studies. RESULTS: In this study, the transcriptome of cup-shaped galls and its host leaf were de novo assembled. Cellular functional enrichment and differentially expressed gene groups in the gall tissues were analyzed. The genes associated with primary metabolism, including photosynthesis, cell wall turnover, and sugar degradation, were expressed differently in galls and leaves. The examination of gene expression demonstrated that the genes involved in brassinosteroid synthesis and responses exhibited a remarkable modulation in cup-shaped galls, suggesting a potential role of steroid hormones in regulating gall development. CONCLUSIONS: This study revealed the genetic responses, including those involved in source-sink reallocation and phytohormone metabolism, of galls induced by a dipteran insect.